Analysis of Nursing Care in Post SC Mothers for Indications of KPD and Breech Location by Implementation of Early Mobilization to Accelerate TFU Reduction - Ani Retni; Sofiyah Tri; Fahmi A. Lihu; Manda Pakaya (PSPP JOURNALS, 2023)
Sectio Caesaria is an artificial birth in which the fetus is born through an incision in the front wall of the abdomen and uterine wall. The uterus must be intact and the fetus must weigh more than 500 grams before the procedure can be performed. Spontaneous leakage of amniotic fluid from the amniotic cavity, where the fetus is housed, is known as premature rupture of membranes. The extended position with the buttocks at the lowest point (breech presentation) is known as the breech position. A downward shift of the uterus that reduces the size of the uterus is known as uterine involution. Early mobility is a postoperative activity that can be carried out in stages, starting with light exercise in bed until you can get out of bed, use the bathroom, and leave the room. By implementing early mobilization to accelerate the decrease in TFU, this study aims to provide nursing care, intervention, implementation, and evaluation for post-cesarean section mothers for indications of premature rupture of membranes and breech presentation at the lowest point. The research method used is observation and descriptive with a nursing care process approach through interviews, observation and documentation. The result of this study, after mobilization interventions the post SC mothers improved or returned to normal and the TFU decreased.